SPECT perfusion imaging in the diagnosis of Alzheimer's disease: a clinical-pathologic study. - Jagust, W; Thisted, R; Devous, MD; Van Heertum, R; Mayberg, H; Jobst, K; Smith, A; Borys, N (2001)
OBJECTIVE: Numerous studies have suggested that temporoparietal hypoperfusion seen on brain imaging with SPECT may be useful in diagnosing AD during life. However, these studies have often been limited by lack of pathologic validation and unrepresentative samples. The authors performed this study to determine whether SPECT imaging provides diagnostically useful information in addition to that obtained from a clinical examination. METHODS: Clinical data and SPECT images were collected prospectively, and patients were followed to autopsy. Clinical history, pathologic findings, and SPECT images were each evaluated by raters blind to other features, and clinical and SPECT diagnoses were compared with pathologic diagnoses. The study population consisted of 70 patients with dementia, followed to autopsy; 14 controls followed to autopsy; and 71 controls (no autopsy performed). The primary outcome was the likelihood of a pathologic diagnosis of AD given a positive clinical diagnosis, a positive SPECT diagnosis, and both. RESULTS: When all participants (patients and controls) were included in the analysis, the clinical diagnosis of "probable" AD was associated with an 84% likelihood of pathologic AD. A positive SPECT scan raised the likelihood of AD to 92%, whereas a negative SPECT scan lowered the likelihood to 70%. SPECT was more useful when the clinical diagnosis was "possible" AD, with the likelihood of 67% without SPECT, 84% with a positive SPECT, and 52% with a negative SPECT. Similar results were found when only patients with dementia were included in the analysis. CONCLUSIONS: In the evaluation of dementia, SPECT imaging can provide clinically useful information indicating the presence of AD in addition to the information that is obtained from clinical evaluation.